Discapacidad, Locura y Educación: A Propósito de un Caso de Segregación en la Universidad Argentina - Sebastian Ariel Rositto (Oñati Socio-Legal Series)
In this paper, a brief historical overview is made according to lifestyles, standards and conceptions of disability over the ages. Next, we will examine regulations concerning disability in higher education. Finally, we will reflect on the National University of Rosario and its School of Law in terms of mental disability.